Individual entrepreneurial orientation (IEO) of university students / Koe Wei-Loon - Koe, Wei-Loon (Universiti Teknologi MARA (UiTM), 2015)
Higher education institutions (HEIs) in Malaysia are expected to produce entrepreneurial graduates and graduate entrepreneurs. However, university students are showing low interest in entrepreneurship. Individual entrepreneurial orientation (IEO) is a crucial competency in becoming a successful entrepreneur, but few studies have scrutinized the issue. Therefore, this paper provides some basic insights on IEO among university students. Based on the questionnaire survey conducted on 157 undergraduates, this paper found that overall students scored highest for innovativeness but lowest for risktaking. Furthermore, business students scored higher in overall IEO, risk-taking, innovativeness and proactiveness than non-business students. However, it only found significant differences in risk-taking and innovativeness between business students and nonbusiness students. This paper concluded that university students were quite innovative but risk-averse. The paper proposed that developing entrepreneurial competency is a crucial strategy in producing entrepreneurial graduates. Specifically, entrepreneurial education or training has to be carefully designed to suit the needs of students from different areas of studies and to equip them with the required competencies.